Risk factors for valgus subsidence in uncemented medial unicompartimental knee arthroplasty - Gallant, Alexander; Vandekerckhove, Pieter-Jan; Beckers, Lucas; De Smet, Arne; Depuydt, Cedric; Victor, Jan; Hardeman, François (Bone & joint open, 2025)
Valgus subsidence of uncemented tibial components following medial unicompartmental knee arthroplasty (UKA) poses a challenge in the early postoperative phase, necessitating a comprehensive understanding of its prevalence, risk factors, and impact on patient outcomes. This prospective multicentre study analyzed 97 knees from 90 patients undergoing UKA across four participating hospitals. A standardized surgical technique was employed uniformly by all participating surgeons. Postoperative evaluations were conducted preoperatively, and one day, four weeks, three months, and one year postoperative, encompassing weightbearing radiographs, bone mineral density assessments, and clinical outcome reports using the Forgotten Joint Score and Oxford Knee Score. Statistical analyses, including non-parametric correlation analysis using the Kendall correlation coefficient and Mann-Whitney U test, were performed to explore associations between subsidence and various patient-related or radiological parameters. A total of eight patients showed more than 2° valgus subsidence (8.2%), higher than previously reported rates. There were significant correlations between subsidence and higher preoperative varus alignment of the tibia, larger adaptation of the preoperative varus to a postoperative neutral or valgus alignment, mediolateral undersizing of the tibial component, excessive lateral load of tibial component by more lateral position of femoral component relative to tibial component, a lower T-score, and female sex. Our study found no significant difference in pain scores between subsidence and non-subsidence groups at various postoperative milestones. These findings corroborate earlier suggested risk factors based on biomechanical models. Further research might provide the opportunity to identify high-risk groups preoperatively and adapt treatment strategies for these patients.